Second Order Limit Language in Variants of Splicing System - Yuhani, Yusof; Muhammad Azrin, Ahmad; Nor Haniza, Sarmin; Fong, Wan Heng (AIP Publishing, 2014)
The cutting and pasting processes that occur in DNA molecules have led to the formulation of splicing system. Since then, there are few models used to model the splicing system. The splicing language, which is the product of splicing system, can be categorized into two, namely the adult and limit language. In this research, limit language is extended to the second order limit language. Few problems are approached which lead to the formation of second order limit language which is then analyzed using various types of splicing system.